Hubungan Antara Status Nutrisi dan Respons Imunologis pada Anak dengan HIV/AIDS di RSUD Wangaya Kota Denpasar: Hasil Penelitian - Runi Arumndari; Asterisa Retno Putri; Claudia Natasha Liman; Made Ratna Dewi; I Wayan Bikin Suryawan (Cermin Dunia Kedokteran, 2024)
Introduction: HIV infection and malnutrition are strongly linked and correlated. Although the exact mechanism is unknown, malnutrition is suspected to disrupt antiretroviral (ART) drug absorption. This research is aimed at determining the relationship between nutritional status and immunological response in children with HIV/AIDS taking ART. Methods: A cross-sectional retrospective analytic study was conducted on 30 children with HIV/AIDS in the pediatric clinic at Wangaya Hospital, using medical record data. The sample was taken with purposive sampling. Nutritional status was defined as poor (weight per height [WHZ] < -2 for children <5 years old and BMI for age [BAZ] <-2 for children ≥5 years old) and good nutrition (WHZ ≥-2 and <+1 for <5 years old children and BAZ ≥-2 and <+1 for ≥5 years old). Immunological response was seen by the increase in CD4 level through a certain time span and categorized into poor (did not increase or increase below the average) and good response (increase above the average). The data was analyzed using Chi-Square. Results: There is no significant relationship between nutritional status and immunological response in children with HIV/AIDS (p = 0.660). There was an almost equal amount of each immunological response category for both good and poor nutritional status. Conclusion: This study showed no difference in immunological response among children with either good or poor nutritional status. Further research on other confounding factors that may affect immunological responses is needed.